Insights of SEDRIC, the Surveillance and Epidemiology of Drug-Resistant Infections Consortium [version 1; peer review: 2 approved] - Paul Turner; Nicholas Feasey; Kate S Baker; Rifat Atun; H. Rogier van Doorn; Francesca Chiari; Andrew Jermy; Timothy Jinks; Matt King; Souha S Kanj; Mirfin Mpundu; Janet Midega; et al. (Wellcome Open Research)
The increasing threat from infection with drug-resistant pathogens is among the most serious public health challenges of our time. Formed by Wellcome in 2018, the Surveillance and Epidemiology of Drug-Resistant Infections Consortium (SEDRIC) is an international think tank whose aim is to inform policy and change the way countries track, share, and analyse data relating to drug-resistant infections, by defining knowledge gaps and identifying barriers to the delivery of global surveillance. SEDRIC delivers its aims through discussions and analyses by world-leading scientists that result in recommendations and advocacy to Wellcome and others. As a result, SEDRIC has made key contributions in furthering global and national actions. Here, we look back at the work of the consortium between 2018-2024, highlighting notable successes. We provide specific examples where technical analyses and recommendations have helped to inform policy and funding priorities that will have real-world impact on the surveillance and epidemiology of infections with drug-resistant pathogens.